IDENTIFICATION AND INTERVENTION OF HEALTH PROBLEMS THROUGH FIELD LEARNING EXPERIENCE (PBL) IN AEK KOTA BATU VILLAGE, NA IX-X DISTRICT, NORTH LABUHANBATU REGENCY - Agustina, Dewi; Situmorang, Irsyad Baihaqi; Rosidah, Seri; Tiana, Triswa; Rizka, Nadia; Rkt, Azkyatul Arifah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This study, conducted through Field Learning Experience (PBL) in Aek Kota Batu Village, North Labuhanbatu Regency, identified Diabetes Mellitus (DM) as a primary and escalating health concern. The rising prevalence of DM is attributed to a confluence of factors, including insufficient public knowledge, unhealthy lifestyle choices, and detrimental environmental conditions. To address this multifaceted issue, a series of targeted interventions were implemented. These interventions encompassed educational outreach programs on DM for adolescents, comprehensive health screenings to facilitate early detection, and the cultivation of Family Medicinal Plants (TOGA). The educational initiatives aimed to enhance understanding of DM, its risk factors, and preventive measures among the younger population. Health screenings played a crucial role in identifying individuals at risk or in the early stages of DM, enabling timely intervention. Furthermore, the promotion and cultivation of TOGA provided a sustainable and natural approach to managing blood sugar levels, fostering self-reliance in health management within the community. The findings underscore the critical importance of collaborative efforts among various stakeholders to effectively mitigate the incidence of DM. This integrated approach, combining education, early detection, and community-based solutions, is essential for improving public health outcomes and reducing the burden of DM in the long term.